Di BOBOto!: First-Time Voters’ Perceptions on Philippine Elections - Capadocia, Cherine M.; Gayosa, Aleth A.; Rivera, Ma. Aissa Francesca J.; Roselo, Aleli G.; Uichanco, Marian Rose P. (Plaridel Journal of Communication, Media, and Society, 2008)
The right of suffrage is considered a vital exercise of democracy, yet not much is known about how voters themselves regard elections. This study addresses this research gap by providing information on how the Filipino youth first-time voters view national elections. It aims to determine the youth’s levels of awareness, knowledge, attitudes, and practices concerning national elections. It also looks into the communication dimension of the youth’s views about the elections. To achieve the study objectives, a survey was conducted among purposively selected students from various universities in Metro Manila. Findings show that television and personal networks are the respondents’ primary sources of election-related information, and that these information sources appear to have greatly influenced their level of knowledge and attitude about elections in the country. Findings further reveal that the respondents did not know much about the Philippine electoral process and they had negative perceptions about elections in the country. They felt that they play a significant role in the elections; however, many of them were not registered voters.